Comparison of Woody Species Diversity and Soil Organic Carbon in Coffee-Based Forests and Natural Forests in Ethiopia - Egeta, Dereje; Ayalew, Semaigzer (CV. Literasi Indonesia, 2025)
Ethiopia is the origin of coffee arabica, which grows in moist Afromontane forests. Today, the expansion of coffee production to adjacent natural forests is high. The current study aims to compare species diversity, richness, regeneration, and soil physico-chemical properties of forests without and with coffee for conservation. A result showed that Forests without coffee have better mean species richness (45.86), Shannon wiener diversity index (2.69), Evenness (0.85), and Simpson (2.94) than forests with coffee. Forests without coffee had a higher percentage of soil carbon storage (mean 147.18) than forests with coffee (Mean 120.25). Forests without coffee are better for all comparisons. Documentation of woody species will be required for both systems for immediate conservation.